2006
DOI: 10.1175/jcli3631.1
|View full text |Cite
|
Sign up to set email alerts
|

GFDL's CM2 Global Coupled Climate Models. Part III: Tropical Pacific Climate and ENSO

Abstract: Multicentury integrations from two global coupled ocean-atmosphere-land-ice models [Climate Model versions 2.0 (CM2.0) and 2.1 (CM2.1), developed at the Geophysical Fluid Dynamics Laboratory] are described in terms of their tropical Pacific climate and El Niño-Southern Oscillation (ENSO). The integrations are run without flux adjustments and provide generally realistic simulations of tropical Pacific climate. The observed annual-mean trade winds and precipitation, sea surface temperature, surface heat fluxes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
299
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(314 citation statements)
references
References 84 publications
13
299
0
2
Order By: Relevance
“…1f) and coupled model SST biases (Fig. 1e) near the Equator has been pointed out in previous studies 30,31 . By conducting control and climate-change experiments with a radiative-flux-corrected CGCM (CCSM3) with realistic present-day coupled SST and comparing the resulting SST projection pattern with the standard CCSM3 greenhouse warming experiment ( Supplementary Fig.…”
supporting
confidence: 81%
“…1f) and coupled model SST biases (Fig. 1e) near the Equator has been pointed out in previous studies 30,31 . By conducting control and climate-change experiments with a radiative-flux-corrected CGCM (CCSM3) with realistic present-day coupled SST and comparing the resulting SST projection pattern with the standard CCSM3 greenhouse warming experiment ( Supplementary Fig.…”
supporting
confidence: 81%
“…One is the stronger easterly winds on the equator which result in stronger equatorial upwelling; another may be weaker activity of tropical instability waves in the ocean. The ocean component MOM4p1 uses the horizontal anisotropic friction scheme from Large et al (2001), which induces more frictional dissipation and prohibits vigorous tropical instability wave activity (Wittenberg et al, 2006). Stronger activity of tropical instability waves could prevent the cold tongue water from cooling down by mixing with the warm off-equatorial water Menkes et al, 2006;Seo et al, 2006;Zhang and Busalacchi, 2008).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This also raises the importance of further improvements on the deep convection parameterization scheme, as the representation of deep convection is central in defining both the dynamical and the heat flux atmospheric feedbacks (Guilyardi et al, 2009). Another possible cause for the excessive ENSO amplitude is the lack of a sufficient surface heat flux damping of SST anomalies in the model, as weaker heat flux damping tends to destabilize and amplify ENSO (Wittenberg, 2002;Wittenberg et al, 2006). Further studies on these topics are warranted.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Tropical climate and ENSO in CM2.1 was initially analyzed by Wittenberg et al (2006) and they found it to be generally realistic although with some limitations. For instance, as many climate models, it has a mean cold bias along the equatorial Pacific and warm bias along the coast of South America, as well as a double ITCZ in the eastern Pacific.…”
Section: The Gfdl Cm21 Modelmentioning
confidence: 99%